The Concept of Infertility in Women: A Narrative Literature Review - Bertha Octarina (Archives of The Medicine and Case Reports, 2023)
Infertility can be defined as a married couple who have not experienced pregnancy for one year, after having regular intercourse 2-3 times a week and without using any preventive methods. There are two types of infertility, namely primary infertility and secondary infertility. Primary infertility is when the wife has never been pregnant even though she has had intercourse without contraception and is faced with the possibility of pregnancy for twelve months. Secondary infertility is when the wife has been pregnant before, but then there is no further pregnancy even though she has had intercourse without contraception and is faced with the possibility of pregnancy for twelve months. Causes of infertility can be divided into three groups. One-third of related problems in women, one-third in men, and one-third are caused by a combination of factors. Infertility in women can be caused by problems with the vagina, cervix uteri, fallopian tubes, uterus, or ovaries. This literature review aimed to describe the definitions, types, and current management of infertility in women.